(untitled) (Texas Journal of Medical Science, 2022)
Patients diagnosed with obstructive hypertrophic cardiomyopathy who have not responded favorably to medical treatment may be good candidates for septal reduction therapy. The purpose of this study was to discover whether or not the Patients who take the oral myosin inhibitor mavacamten have the ability to improve to the point where they no longer require septal reduction treatment. This is true regardless of whether or not the patients opt to abandon the medicine completely. Methods: Patients who satisfied the requirements for septal reduction therapy and had a left ventricular outflow tract gradient of 47 mm Hg at rest or during provocation were randomly assigned, in a double-blind fashion, to receive either 5 milligrams of mavacamten per day or a placebo. Patients needed to have a gradient in their left ventricular outflow tract that was 47 mm Hg in order for them to be eligible for the treatment. The patients’ left ventricular outflow gradients and ejection fractions were used to determine how much of the dose should be increased up to 15 mg. The primary outcome was a composite measure that was taken after 20 weeks of treatment to determine the proportion of patients who either got septal reduction therapy or fulfilled the eligibility requirements. Results: Totally, 121 individuals with obstructive hypertrophic cardiomyopathy participated. The patients’ mean age was 58, 66% were men, and 88% had a left ventricular outflow gradient of 84 mm Hg or more after exercise. 43 of 56 placebo patients (68.4%) met guideline criteria or received septal reduction treatment after 20 weeks, whereas only 10 of 56 mavacamten patients (17.9%) did, a 45.4% difference (95 percent confidence interval: 33.4 percent -80.4 percent; P 0.03). Secondary testing found statistically significant differences (P less than 0.001). Conclusion: After 20 weeks of treatment, mavacamten decreased the number of obstructive hypertrophic cardiomyopathy patients with refractory symptoms who needed septal reduction. Septal reduction therapy may be unnecessary in the long term.